2014
DOI: 10.1159/000366308
|View full text |Cite
|
Sign up to set email alerts
|

Des-γ-Carboxy Prothrombin (DCP) as a Potential Autologous Growth Factor for the Development of Hepatocellular Carcinoma

Abstract: Des-γ-carboxy prothrombin (DCP) is a prothrombin precursor produced in hepatocellular carcinoma (HCC). Because of deficiency of vitamin K or γ-glutamyl carboxylase in HCC cells, the 10 glutamic acid (Glu) residues in prothrombin precursor did not completely carboxylate to γ-carboxylated glutamic acid (Gla) residues, leaving some Glu residues remained in N-terminal domain. These prothrombin precursors with Glu residues are called DCPs. DCP displays insufficient coagulation activity. Since Liebman reported an el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 67 publications
1
33
0
Order By: Relevance
“…In our study, we showed that higher serum concentrations of both PIVKA-II and AFP, were significantly-related to diagnosis of HCC. This is in accordance with other authors, who showed the production of PIVKA-II by HCC and its role as an autologous growth, invasive and pro-angiogenetic factor (11-13) as well as its absence in non-neoplastic hepatic diseases (10).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, we showed that higher serum concentrations of both PIVKA-II and AFP, were significantly-related to diagnosis of HCC. This is in accordance with other authors, who showed the production of PIVKA-II by HCC and its role as an autologous growth, invasive and pro-angiogenetic factor (11-13) as well as its absence in non-neoplastic hepatic diseases (10).…”
Section: Discussionsupporting
confidence: 93%
“…PIVKA II is not elevated in benign hepatic diseases (e.g. cirrhosis, necrosis) (10,18), while it is elevated in HCC at early stage as well as in HCC nodules of all sizes (8,18,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The half of new cases of death occurs in China every year [1][2][3]. The prognosis of patients with HCC is poor and once HCC invades other organs and tissues or spreads distantly, the clinical outcome may be even worse [4][5]. Therefore, early detection of HCC is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, DCP continues to be used as a diagnostic marker, and DCP is also a promising target for development of HCC chemotherapy. Development of DCP inhibitors and their use might improve the efficacy of gefitinib and many other tyrosine kinase inhibitors for the treatment of HCC [20,41]. …”
Section: Discussionmentioning
confidence: 99%